Implementation of Elementary School Supervisory Duties in Turi, Pakem, and Cangkringan Sub-districts - Endang Sri Budi Herawati; Endra Sayekti (Journal of Educational Studies, 2025)
The implementation of elementary school supervision has undergone a paradigm shift from evaluative supervision to collaborative mentoring oriented towards improving the quality of education. In this context, supervisors are required not only to carry out control functions but also to act as professional facilitators who provide continuous support to schools. Therefore, it is important to examine how supervision is carried out in accordance with the mentoring cycle, as well as the challenges and strategies that accompany it. This study used a qualitative approach with data collection techniques through interviews, observation, and documentation. The research subjects included elementary school supervisors in the Kapanewon Turi, Pakem, and Cangkringan areas of Sleman Regency. Data were analyzed descriptively through data reduction, data presentation, and conclusion drawing to obtain a comprehensive picture of the implementation, challenges, and strategies of supervision. The results of the study indicate that supervision implementation has been in accordance with the mentoring cycle, which includes planning, program planning mentoring, program implementation mentoring, and reporting. Supervisory practices have moved towards a data-driven, collaborative, and reflective approach. However, supervisors face various challenges, such as the vast area of supervision, the large number of schools, and a high administrative burden. To address this, supervisors implemented adaptive strategies such as prioritizing mentoring, utilizing communication technology, and flexible time management. The implementation of elementary school supervision has been carried out in accordance with applicable regulations and demonstrates a transformation toward collaborative, professional supervision practices. Despite facing various limitations, supervisors were able to develop adaptive and contextual strategies so that the mentoring process remains effective in supporting the continuous improvement of educational quality.